Profil Kepribadian Muslim Digital: Integrasi Dzikir, Fikir, Ilmu dan Amal - Muluk, Muchamad Saiful (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
The digital age is an absolute requirement that presents both benefits and challenges. It has a direct impact on all aspect of modern life, including Muslim lives, as well as social and individual behavior. The optimal Muslim personality profile for navigating modern society and daily life in the digital age is addressed by this research. Using library research methodologies, a descriptive-qualitative methodology was used to perform this study. The results showed that 1) the Muslim personality is formed by the mechanism of balancing the role of the personality structure between the sharpness of reason (al-aql), the gentleness of the heart (al-qalb), and the control of lust (al-nafs) in the Muslim soul; 2) the ideal Muslim personality in the digital era is a person who integrates zikr (remembrance), fikr (thinking), ilm (knowledge), and 'amal (charity) in daily life; and 3) the implementation of the ideal Muslim personality produces individual piety and social piety, which are needed in building a harmonious and serene digital society, both as individuals and members of society.